Analysis of Factors Affecting the Sustainability Performance of Islamic Banks in ASEAN - Angelica, Zahwa; Oktaviana, Ulfi Kartika (Moneter: Jurnal Keuangan dan Perbankan, 2024)
This study focuses on the challenges faced by the global banking industry, including economic fluctuations and supply chain disruptions, which impact the Islamic banking sector in ASEAN. Although its contribution is small, the growth potential of Islamic banks in ASEAN is very large. Therefore, it is essential to examine the factors that affect the sustainability performance of Islamic banks in the region. This study aims to analyze the effects of financial performance, risk management, and technology on the sustainability of Islamic banking in ASEAN. The sample comprises 27 Islamic banks from ASEAN, selected through purposive sampling methods, including institutions from Indonesia, Malaysia, Brunei, and the Philippines. The quantitative research approach with panel data analysis was carried out using EViews 13 software. The findings indicate that financial performance and technology significantly influence sustainability performance, while only the financial performance variable demonstrates a notable effect on sustainability. Conversely, the variables of risk management and technology do not show a significant impact on sustainability performance. Overall, financial performance, risk management, and technology simultaneously influence the sustainability of Islamic banking performance, highlighting the interaction of these factors in enhancing sustainability in ASEAN.